Automated Laboratory and Field Techniques to Determine Greenhouse Gas Emissions - Zaman, M.; Kleineidam, K.; Bakken, L.; Berendt, J.; Bracken, C.; Butterbach-Bahl, Klaus; Cai, Z.; Chang, S.X.; Clough, T.; Dawar, K.; Ding, W.X.; Dörsch, P.; et al. (Springer, 2021)
Methods and techniques are described for automated measurements of greenhouse gases (GHGs) in both the laboratory and the field. Robotic systems are currently available to measure the entire range of gases evolved from soils including dinitrogen (N 2 ). These systems usually work on an exchange of the atmospheric N 2 with helium (He) so that N 2 fluxes can be determined. Laboratory systems are often used in microbiology to determine kinetic response reactions via the dynamics of all gaseous N species such as nitric oxide (NO), nitrous oxide (N 2 O), and N 2 . Latest He incubation techniques also take plants into account, in order to study the effect of plant–soil interactions on GHGsand N 2 production. The advantage of automated in-field techniques is that GHG emission rates can be determined at a high temporal resolution. This allows, for instance, to determine diurnal response reactions (e.g. with temperature) and GHG dynamics over longer time periods.